2019
DOI: 10.1182/blood-2018-04-843425
|View full text |Cite
|
Sign up to set email alerts
|

The von Willebrand factor Tyr2561 allele is a gain-of-function variant and a risk factor for early myocardial infarction

Abstract: The frequent von Willebrand factor (VWF) variant p.Phe2561Tyr is located within the C4 domain, which also harbors the platelet GPIIb/IIIa-binding RGD sequence. To investigate its potential effect on hemostasis, we genotyped 865 patients with coronary artery disease (CAD), 915 with myocardial infarction (MI), and 417 control patients (Ludwigshafen Risk and Cardiovascular Health Study) and performed functional studies of this variant. A univariate analysis of male and female carriers of the Tyr2561 allele aged 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 39 publications
1
30
0
1
Order By: Relevance
“…Nevertheless, they could be detected when aggregate motion tracking of images was implemented. This visualization approach, consisting of the superposition of several images of different times, has been proven successful in visualizing rolling vWF-based conglomerates ( 31 , 85 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, they could be detected when aggregate motion tracking of images was implemented. This visualization approach, consisting of the superposition of several images of different times, has been proven successful in visualizing rolling vWF-based conglomerates ( 31 , 85 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hemodynamic forces in the circulation stretch ULVWF or immobilized VWF to a more extended configuration to enhance platelet binding, which may induce thrombosis formation (Schneppenheim et al , 2019), and to expose the cryptic proteolytic site in the A2 domain for cleavage by ADAMTS13 (Furlan et al , 1996; Tsai, 1996; Zhang et al , 2009; Wu et al , 2010), which may reduce VWF activity. Here we further demonstrated that mechanical forces modulate VWF–ADAMTS13 interaction when the enzyme and the substrate come into rapid, repetitive, but brief contacts, which is likely to occur in flowing blood.…”
Section: Discussionmentioning
confidence: 99%
“…As further explanation, functional variants of VWF have been identified, which elicit differences in the protein conformation and shear sensitivity. These variants are associated with increased platelet aggregate size and the occurrence of these VWF variants correlates with a higher risk of thromboembolisms including myocardial infarction and stroke (82). In line with these observations, it can be assumed that bacterial interaction with VWF might effect the hemostatic function in various ways, i.e., by sterical hindrance of the platelet binding site, by alteration of the VWF conformation, and by inhibition of dimerization and multimerization activities, thereby increasing the risk for cardiovascular complications.…”
Section: Effect Of Staphylococcal and Streptococcal Interaction With mentioning
confidence: 99%